Risk of Diabetes Mellitus in Persons with and without HIV: A Danish Nationwide Population-Based Cohort Study - Rasmussen, Line D.; Mathiesen, Elisabeth R.; Kronborg, Gitte; Pedersen, Court; Gerstoft, Jan; Obel, Niels (PloS one, 2012)
In a nationwide, population-based cohort study we assessed the risk of diabetes mellitus (DM) in HIV-infected individuals compared with the general population, and evaluated the impact of risk factors for DM in HIV-infected individuals. We identified 4,984 Danish-born HIV-infected individuals from the Danish HIV Cohort Study and a Danish born population-based age- and gender-matched comparison cohort of 19,936 individuals (study period: 1996-2009). Data on DM was obtained from the Danish National Hospital Registry and the Danish National Prescription Registry. Incidence rate ratios (IRR) and impact of risk factors including exposure to Highly Active Antiretroviral Therapy (HAART) and antiretroviral drugs were estimated by Poisson regression analyses. In the period 1996-1999 risk of DM was higher in HIV-infected individuals compared to the comparison cohort (adjusted IRR: 2.83; 95%CI: 1.57-5.09), both before (adjusted IRR: 2.40; 95%CI: 1.03-5.62) and after HAART initiation (adjusted IRR: 3.24; 95% CI: 1.42-7.39). In the period 1999-2010 the risk of DM in HIV-infected individuals did not differ from that of the comparison cohort (adjusted IRR: 0.90; 95% CI: 0.72-1.13), although the risk was decreased before HAART-initiation (adjusted IRR: 0.45; 95%CI: 0.21-0.96). Increasing age, BMI and the presence of lipoatrophy increased the risk of DM, as did exposure to indinavir, saquinavir, stavudine and didanosine. Native HIV-infected individuals do not have an increased risk of developing DM compared to a native background population after year 1998. Some antiretroviral drugs, not used in modern antiretroviral treatment, seem to increase the risk of DM.